Changing trend of peasant behavior in Russia during Stolypin's agrarian reform / Tendência de mudança do comportamento de camponeses na Rússia durante as reformas agrárias de Stolypin - Kuznetsov, Dmitry V. (Revista de Direito da Cidade, 2023)
Abstract In this article, the authors aim to differentiate various categories of the peasantry according to the views on property to develop an optimal research approach that will allow for an objective and comprehensive analysis of the attitudes and behavior of the peasant population of Russia during the Stolypin course of agrarian policy pursued by the autocracy. The study shows the validity of using the peasantry's attitude to property as one of the key criteria for assessing the degree of efficiency of the Stolypin reform. The selected criterion allows one to show the evolution of this attitude depending on the social characteristics of a particular category of peasants. Any reform should be assessed from the standpoint of those whose interests are affected first. Property is one of the main guidelines that determine the position of a person in society and the world. Aimed at creating the stratum of steady owners in the village, P.A. Stolypin's reform frees the peasants from the petty fiscal and bureaucratic oversight of the state. As the peasantry realizes the seriousness of the government's intentions and possible prospects for the development of the economy, their attitude to the reform also changes. This change takes place along with the peasantry's realization that the state is interested in steady owners in the village. Those who can and want to be one, accept the reform with enthusiasm, others ultimately see in the reform an opportunity to shift the blame for their failure to the state. Keywords: Capitalist element; Classification, community; Main categories; Semifeudal ways of exploitation. Resumo Neste artigo, os autores buscam diferenciar várias categorias de do campesinato de acordo com os pontos de vista sobre a propriedade para desenvolver uma abordagem de investigação que permita uma análise objetiva e abrangente das atitudes e comportamento da população camponesa da Rússia durante o período de Stolypin de política agrária estabelecida pela autocracia. O estudo mostra a validade de utilizar a postura dos camponeses em relação à propriedade como um dos critérios-chave para avaliar o grau de eficiência da reforma Stolypin. O critério selecionado permite mostrar a evolução desta postura em função das características sociais de uma categoria particular de camponeses. Qualquer reforma deve ser avaliada do ponto de vista daqueles cujos interesses são afetados em primeiro lugar. A propriedade é uma das principais orientações que determinam a posição de uma pessoa na sociedade e no mundo. Com o objetivo de criar o estrato de proprietários estáveis na aldeia, a reforma de P.A. Stolypin liberta os camponeses da fiscalização fiscal e burocrática mesquinha do Estado. À medida que os camponeses se apercebem da seriedade das intenções do governo e das possíveis perspectivas de desenvolvimento da economia, a sua posição em relação à reforma também muda. Esta mudança tem lugar juntamente com a percepção do campesinato de que o Estado está interessado em ter proprietários estáveis na aldeia. Aqueles que podem e querem ser um, aceitam a reforma com entusiasmo, outros acabam por ver na reforma uma oportunidade de transferir as culpas do seu fracasso para o Estado. Palavras-chave: capitalismo, classificação, comunidade, principais categorias, formas de exploração semifeudal